The genetic structure and admixture of Manchus and Koreans in northeast China - Na Sun; Le Tao; Rui Wang; Kongyang Zhu; Xiangjun Hai; Chuan-Chao Wang (Taylor & Francis Group, 2023)
Background The fine-scale genetic profiles and population history of Manchus and Koreans remain unclear. Aim To infer a fine-scale genetic structure and admixture of Manchu and Korean populations. Subjects and methods We collected and genotyped 16 Manchus from Liaoning and 18 Koreans from Jilin province with about 700K genome-wide SNPs. We analysed the data using principal component analysis (PCA), ADMIXTURE, Fst, TreeMix, f-statistics, qpWave, and qpAdm. Results Manchus and Koreans showed a genetic affinity with northern East Asians. Chinese Koreans showed a long-term genetic continuity with Bronze Age populations from the West Liao River and had a strong affinity with Koreans in South Korea and Japan. Manchus had a different genetic profile compared with other Tungusic populations since the Manchus received additional genetic influence from the southern Chinese but didn't have West Eurasian-related admixture. Conclusions The genetic formation of Manchus involving southern Chinese was consistent with the extensive interactions between Manchus and populations from central and southern China. The large-scale genetic continuity between ancient West Liao River farmers and Koreans highlighted the role farming expansion played in the peopling of the Korean Peninsula.